Serial testing of health care workers for tuberculosis infection: A prospective cohort study - Casas, Irma (PLoS One, 2020)
Health Care Workers (HCW) may have an occupational risk of latent tuberculosis infection (LTBI) and TB disease. The objective of this study was to evaluate the performance of the 2-step strategy: tuberculin skin test (TST) followed by confirmation with Interferon (IFN)-γ- release assays (IGRAs) in HCW. A secondary objective was to determine the factors related to conversions and reversions. HCW at risk of occupational exposure who attended the Occupational Department of the Hospital Germans Trias i Pujol were included during the study period (2013–2016). All professionals testing negative for LTBI were included in a cohort study. These workers were followed up with the administration of a TST and an IGRA quantification at least one year after inclusion in the study. Workers with positive TST, regardless of the results of the IGRA tests, were followed-up with an IGRA. 255 workers were enrolled in the study and 108 workers from the same cohort were followed up. During the follow-up period, seven workers presented TST test conversion. One of these conversions was also confirmed by an IGRA test. There were 2 conversions of cases only testing positive with the IGRA. There have been only 2 reversions of cases testing negative with the IGRA. In this study, not all TST conversions were confirmed when using the IGRA test, which highlights the importance of the 2-step strategy. We have detected a low number of conversions and reversions. Our conclusions should be confirmed in studies with a longer follow-up time.